Prototypical model of a discursive personality within the theory of values-based sociodiscourse - Soloshchuk, Lyudmila; Skrynnik, Yuliia (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2024)
In this theoretical study the concept of the prototypical model of a discursive personality within the framework of the theory of values-based sociodiscourse is explored. The prototypical model, as conceived within this theory, represents a multidimensional structure that enables the analysis of values, roles, identity, and interpersonal interactions, all of which contribute to the formation of a personality in contemporary society. The model underscores the significance of values as guiding principles that shape an individual’s construal of the world.The prototypical model of a discursive personality within the theory of values-based sociodiscourse can be described as a conceptual framework where a discursive personality is shaped by multiple sociocultural factors. These factors include the types of discourse individuals engage in (everyday, institutional), their value orientations (such as belonging to a social group, love, esteem, and self-actualization), and social factors (social status, role, and gender). The social parameters play a crucial role in determining how individuals navigate and express their values through discourse. The framework also categorizes discursive personalities into participants, attractors, and creators, with each type exhibiting distinct verbal, non-verbal, and supra-verbal repertoires associated with each type of discursive personalities.A key aspect of the multifaceted prototypical model of a discursive personality is its integration within the sociocultural context. This dimension is visually depicted through the stance of a discursive personality and discursive practices as central elements within the sociocultural mechanism. The study offers definitions of discourse and a discursive personality within the theory of values-based sociodiscourse framework, providing a foundation for future research. Further investigations in this area could enhance our understanding of how values shape a discursive personality and his / her behavior across various social contexts.